Implementasi IKM Berdasarkan PERMENPAN RB Nomor 14 Tahun 2017 Sebagai Wujud Pelayanan Prima - Ni Putu Dyah Erna Savitri; Arif Devi Dwipayana; Yusime Fitasari (Journal of Research and Development on Public Policy, 2023)
Law of the Republic of Indonesia No. 25 of 2004 mandates the Community Satisfaction Index (IKM) as a benchmark for assessing the quality of public services. UPT PKB Malang City which provides services in the field of Motorized Vehicle Testing, needs to measure IKM. The last evaluation in 2020 showed a "GOOD" value, but did not pay attention to the latest regulations related to IKM, namely Permenpan No.14 of 2017. Previous research has shown that the application of IKM using indicators from Permenpan No.14 of 2017 can increase the level of agency service. So this research aims to further examine the implementation of IKM by referring to Permenpan No.14 of 2017, as a form of excellent service. The method used in this research is to use observational research techniques, interviews and questionnaires. The method of analysis used is quantitative analysis which is generated based on quantitative data obtained through data collection. The results of this study prove that it is important to periodically evaluate IKM with Permenpan No.14 of 2017 regularly in supporting the performance targets of testing agencies and can improve service elements where the IKM value resulting from this study is "75.08" having quality "poor" service.